Memahami mekanisme berpikir melalui neuro-linguistic programming untuk memperkuat deep learning di sekolah dasar - Riyadi, Arie Rakhmat; Maulida, Aya Shofia; Ginting, Lea Christina Br; Sa’ud, Udin Syaefudin; Dwidianti, Kania; Gifari, Muhammad Rizky Al; Sholihat, Nawaina Pitria; Riyadi, Diki; Ridhlah, Nazfa Laila (KHIDMAH : Jurnal Pengabdian Masyarakat, 2025)
This article addresses the importance of teachers’ understanding of students’ thinking mechanisms as the basis for implementing deep learning in elementary schools. In Garut Regency, Indonesia, many teachers still rely on conventional teaching methods, leading to passive learning and low student engagement. To respond to this challenge, a community service program (PkM) was designed to enhance teachers’ competence through the application of Neuro-Linguistic Programming (NLP). The program employed a hybrid model, including online conceptual sessions on NLP and deep learning as well as offline workshops, collaborative practices, and classroom simulations. Participants consisted of elementary school teachers from various districts in Garut, selected based on their commitment to implementation. Data were collected through pre-test and post-test instruments and perception surveys. The results indicated a significant improvement in teachers’ ability to identify students’ learning modalities, apply NLP techniques and design mindful, meaningful, and joyful learning experiences. Teachers also reported positive perceptions of NLP as a tool to foster inclusivity, motivation, and social-emotional development in classrooms. In conclusion, the program effectively strengthened teachers’ pedagogical competence and demonstrated the potential of NLP as an innovative approach to improve the quality of elementary education in Indonesia.